A case study on Participatory Health Planning and Budgeting in Somali Region of Ethiopia - Oladeji Olusola; Mahamed Sharif; Mohammed Omer; Ann Robins (Archives of Current Research International, 2022)
Participatory planning and budgeting aims to democratically allocate public money for local services, enabling communities to decide how public funds are spent and the monitoring of the services. This case study described the process and outcome of a pilot project on participatory planning and budgeting in the health sector in 6 project woredas (districts) in Somali region of Ethiopia. The Social Accountability Committee members were selected using the World Bank’s framework on accountability. The community members represented by the actively participated in all stages of the planning and budgeting process leading to the development of woreda health Joint Action Plans (JAPs) which are community prioritized health activities. Eighteen (49%) of the 37 activities in the Joint Action Plans were included in the woreda annual health budget which ranged from 29% to 80% across the 6 woredas. In addition, during the first half of the fiscal year, implementation has started in 10 (56%) of the 18 JAPs activities budgeted in the annual health woreda plans and ranged from 0% to 75% across the 6 woredas. The study highlighted the feasibility of engaging the community in participatory planning and budgeting process which resulted in allocation of woreda annual health budget to some of the prioritized items in the Joint Action Plans. In the bid to ensure sustainability, government ownership and ensure citizens’ participation, the fund for the participatory budgeting process should be included in the woreda annual budget and proportion of the annual budget should be designated to the implementation and monitoring of the Joint Action Plans through appropriate legislation.